Managing emergency department crowding through improved triaging and resource allocation - YANG, Kum Khiong (Institutional Knowledge at Singapore Management University, 2016)
Long waiting times in emergency departments (EDs) not only reduce patients’ perceived quality of care, but also increase crowding which can adversely affect patients’ outcomes. Waiting time has been found to affect patients’ outcomes and is closely associated with delays in the provision of ancillary services to ED patients by the diagnostic/treatment laboratories. The focus of this study is to improve the flow of ED patients by testing alternative triage processes and capacity of physicians, triage nurses and laboratories. Three alternative triage processes are examined for managing the flow of ED patients through shared and dedicated laboratories across different utilization of physicians, triage nurses, and laboratories using a discrete event simulation (DES) model that captures the pertinent characteristics of EDs operating in tertiary acute care hospitals under conservative assumptions. Our results show that choosing the appropriate triage process and adding extra capacity to the triage and dedicated laboratory can significantly improve ED performance, especially when physician utilization is high. In contrast, adding extra capacity to a shared laboratory improves performance only slightly. Our results also show that shared laboratory generally provides better support to EDs than dedicated laboratory.